A Novel Microduplication Spanning Exons 8–16 of ATP2C1 That Was Undetectable by Standard Sanger Sequencing in a Japanese Patient With Hailey–Hailey Disease - Teye, Kwesi; Koga, Hiroshi; Hamada, Takahiro; Matsuda, Mitsuhiro; Ichiki, Mikio; Numata, Sanae; Ishii, Norito; Nakama, Takekuni (Frontiers in Medicine, 2020)
Hailey-Hailey disease (HHD) is genetic skin disorder characterized by repeated and exacerbated skin lesions in friction regions. ATP2C1, encoding SPCA1, was demonstrated to be the responsible gene for HHD pathogenesis. However, for some cases, no ATP2C1 mutation could be determined by standard Sanger sequencing, thereby obscuring the cause and diagnosis of HHD. In this study, we investigated the possibility that HHD is caused by complex ATP2C1 defects using MLPA analysis for 10 out of 50 cases in our institute without ATP2C1 mutations. In one female Japanese patient and her father, who also show HHD, MLPA followed by PCR analyses revealed a novel duplication of exons 8-16 of ATP2C1. The duplication was predicted to add 20615 bp, 882 nt and 294 amino acid residues to the genome, mRNA and SPCA1 protein, respectively. By RT-PCR using patient skin RNA, we could confirm that a larger transcript was produced and we found that the abundance of the normal transcript was clearly reduced in the patient. Putative structures of wild-type and duplicated proteins revealed differences in arrangement of SPCA1 domains that may have functional consequences. Strikingly, the phosphorylation and the nucleotide-binding domains were interrupted by insertion of a partial actuator, transmembrane and phosphorylation domains. The additional 294 amino acids appear to disrupt SPCA1 structure and function, causing HHD. Our study expands the spectrum of genetic defects in HHD and showed that disruption of SPCA1 structure and function by the microduplication caused HHD in the patient and her father.